Ready to eat dry foods refrigerated meals, shelf stable food etc mixes like cake mixes are all examples of convenience foods in Nigeria. Organoleptic properties of food such as color, taste, flavor, aroma, and texture have distinct and influential effect on food acceptability and specifically influence the decision that a consumer makes regarding the preference of food substance. Despite being a rich source of complex carbs vitamins and minerals, plantains are quite simple to digest. It serves only as a replacement side dish and is often consumed with other foods. It has not yet been completely developed to create snack items in terms of vitamins and other nutrients. This study aimed at investigating the proximate and organoleptic analysis of plantain mosa and puff-puff and specifically compared the level of their acceptability. Proximate analysis of plantain mosa and puff-puff were carried out in the Laboratory to ascertain their level of composition of moisture content, protein,fat,ash, crude fibre and carbohydrate. One hundred samples of sensory evaluation forms were administered to respondents comprising of all kind of visitors at University of Ibadan Hotel under University of Ibadan ventures in its environ to assess the organoleptic properties of plantain mosa and puff-puff to determine most preferred sample. Random and convenience sampling were used to determine the respondents at the hotel. Data were analyzed using descriptive statistics (use of charts and percentage). The findings included variations in the proximate analysis value of Plantain mosa and puff-puff. (2024)
Chin-chin is a popular snack across Nigeria made from wheat flour and fried with fats/oils or sometimes baked. It is regarded as being nutritionally poor, as cereal wheat lacks essential amino acids such as lysine and threonine, hence substituting wheat flour with cheap staples, such as cereals, tubers and pulses; helps increase the nutritional quality of food products. However, chin-chin made from sweet potato and cowpea composite flour has not gained a high level of popularity and acceptance from the public compared to wheat flour chin-chin. Only a few percentage of people know about the potential of making confectionary and snacks food using sweet potato and the range of essential nutrients in the sweet potato flour that is lacking in processed wheat flour and how this sweet potato and cowpea flour can be easily produced and raw materials readily available in the open market. This study was aimed at evaluating the overall acceptability of chin -chin made with sweet potato –cowpea flour and the awareness of sweet potato – cowpea flour chin-chin as compared to the popular wheat flour chin-chin. The study was carried out in the University of Ibadan. Structured questionnaire (sensory evaluation form) was administered to respondents. The overall acceptability showed that sweet potato – cowpea flour was well accepted by respondents. The color, taste, aroma, texture of the snack were rated high by respondents. The level of awareness and consumption of sweet potato –cowpea flour chin-chin was assessed and it was observed that a large percentage of the respondent were not aware that chin-chin can be made with any other type of flour (in this case sweet potato-cowpea flour) other than wheat flour and have never eaten sweet potato –cowpea flour chin-chin.